Analisis Kebijakan Pemberian Insentif Pajak atas Sumbangan dalam Kegiatan Penelitian dan Pengembangan - Firmansyah, FIRMANSYAH (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2011)
The research aims to analyze the tax incentive policy for the donation given to research and development activities in Indonesia, as stated in Law No. 36 of 2008 on the Income Tax. The research is descriptive and uses qualitative approach. The result of the research shows that the tax incentive policy for the donation given to research and development activities in Indonesia successfully increases the number of donations and therefore support the increase of innovative products of the research and development activities.